Co‐sensitization of Organic Dyes for Efficient Dye‐Sensitized Solar Cells. Issue 1 (27th November 2012) - Cheng, Ming; Yang, Xichuan; Li, Jiajia; Zhang, Fuguo; Sun, Licheng
Abstract Novel cyanine dyes, in which a tetrahydroquinoline derivative is used as an electron donor and 1‐butyl‐5‐carboxy‐3, 3‐dimethyl‐indol‐1‐ium moiety is used as an electron acceptor and anchoring group, were designed and synthesized for application in dye‐sensitized solar cells. The photovoltaic performance of these solar cells depends markedly on the molecular structure of the dyes in terms of the n‐hexyl chains and the methoxyl unit. Retardation of charge recombination caused by the introduction of n‐hexyl chains resulted in an increase in electron lifetime. As a consequence, an improvement of open‐circuit photovoltage (Voc) was achieved. Also, the electron injection efficiencies were improved by the introduction of methoxyl moiety, which led to a higher short‐circuit photocurrent density (Jsc). The highest average efficiency of the sensitized devices (η) was 5.6 % (Jsc=13.3 mA cm−2, Voc=606 mV, and fill factor FF=69.1 %) under 100 mW cm−2 (AM 1.5G) solar irradiation. All of these dyes have very high absorption extinction coefficients and strong absorption in a relatively narrow spectrum range (500–650 nm), so one of our organic dyes was explored as a sensitizer in co‐sensitized solar cells in combination with the other two other existing organic dyes. Interestingly, a considerably improved photovoltaic performance of 8.2 % (Jsc=20.1 mA cm−2, Voc=597 mV, and FF=68.3 %) was achieved and the device showed a panchromatic response with a high incident photon‐to‐current conversion efficiency exceeding 85 % in the range of 400–700 nm.